"V Televisión", birth of a private regional channel in Galicia. Research of the information formats - López Bolás, Alba; Román Portas, Mercedes (Historia y Comunicación Social, 2014)
The private regional channel of Galicia, V Televisión, start broadcasting in May 2010 from the hand of Grupo Voz. In this paper we analyze their information formats in order to determine their capacity to adapt to new audiovisual landscape. The goal is to see why failed the initial channel idea arise mainly as a being informative, and how they have managed to capture a specific audience centralizing most of its resources on a program of analysis and discussion (Vía V) and with an effective strategy on Internet and social networks.
Keywords: V Televisión; news formats; Galicia.